ANALYSIS OF DESCRIPTIVE QUESTIONS IN DAILY TESTS FOR THE MATHEMATICS SUBJECT IN NINTH GRADE OF JUNIOR HIGH SCHOOL - Barus, Aferbina; Siregar, Tiur Malasari; Umri, Fasya Maharani; Rajagukguk, Jesika Replesia; Nur Hidayah Aini; Siahaan, Yuni Apriani (Universitas Muhammadiyah Metro, 2026)
The purpose of this study was to determine the quality of daily test items in mathematics subjects on SPLDV material for class IX in the 2024/2025 school year. The research method applied in this research is quantitative descriptive method, with samples in the form of 16 student answer sheets and question sheets. Data were collected through interviews conducted with Mathematics subject teachers, to find out the purpose and technique of preparing questions using documentation techniques copies of description question sheets and student answer sheets. Analysis of validity, reliability, difficulty level, and distinguishing power was carried out to determine the quality of the items. The results showed that in the validity analysis, there were 3 questions that were declared valid and one invalid. The results of the reliability analysis, the question was low with a Cronbach's Alpha value of 0,492, indicating weak inter-item consistency. The results of the difficulty level analysis showed that three questions were classified as easy (index 0,71–1,00), and one question was classified as moderate. And the results of the differentiating power analysis, the four description items have good differentiating power.